The complete resource on pediatric office emergency preparedness - Shenoi, Rohit (SpringerBriefs in Public Health, 2013)
Pediatric practice can be hectic under optimal everyday conditions. Imagine what can happen when a child has an asthma attack, is choking, or goes into cardiac arrest. The efficient pediatric provider not only needs to have current knowledge of tools and skills, but must also be prepared to use them in the most relevant and up-to-date manner in a crisis.  The Complete Resource on Pediatric Office Emergency Preparedness expands the pediatric primary care physician's role by focusing on coordinated care practice, specifically working in tandem with staff and EMS crews. This handbook-and-video set gives readers protocols for best office-based practices for common emergencies (e.g., head injuries) and special cases (e.g., disasters). Its print guide identifies basic medications (with indications and dosing instructions), equipment, and life support procedures for optimum emergency preparedness, and the video fleshes out these concepts with how-to and not-to case vignettes. The package models current educational methods, both for learning and for teaching skills to professionals and parents.   Key features of The Complete Resource:   Protocols for common pediatric office emergencies. Protocols for special situations: children with special care needs, psycho-social emergencies, disasters. Instruction on basic life support skills. Videos illustrating do's and don'ts of emergency response. Quality improvement and learning assessment materials. A family education unit on health emergencies and first aid.   The Complete Resource on Pediatric Office Emergency Preparedness is a necessary addition to the pediatrician's education library, and should be of particular interest to researchers in maternal and child health.